Pembuatan Busana Excotic Dramatic dengan Bahan Batik Lereng, Santung dan Anyaman Kulit Sintetis - Della Kartika; Edi Suwasana (Garina, 2024)
Exotic Dramatic fashion, this fashion reflects a person's gentle personality, as well as a firm and strong side in some situations. Exotic dramatic clothing can be worn on formal or non-formal occasions. The problem that will be discussed is how the process of making exotic dramatic clothing with slope batik, santung and synthetic leather webbing. While the benefits can be to know the manufacture of exotic dramatic clothing with slope batik, santung and synthetic leather webbing. The method used by the author is the R&D method. This exotic dramatic fashion has 3 parts of fashion which include, crop top, dress, custom skirt, with standard size M, making archetypes, breaking patterns, making wicker, preparing tools and materials, sewing. The clothes on the Crop top three-axis wicker technique are located on the front of the bottom and on the back, the combination of slope batik motifs whose patterns are regular slashes and the combination of red and black materials makes an exotic impression. Making this fashion with slope batik, santung and synthetic leather webbing, in making woven size 3 cm wide 65 cm long which is sewn once so that the finished woven product becomes neat and not wavy. In the hollow three-axis webbing, it should be helped by sewing hands outside as a woven barrier on clothes so that they are not easily shifted and the result is neater.